2018
DOI: 10.1002/hbm.24431
|View full text |Cite
|
Sign up to set email alerts
|

The impact of type 1 diabetes on neural activity serving attention

Abstract: Type 1 diabetes has been associated with alterations in attentional processing and other cognitive functions, and previous studies have found alterations in both brain structure and function in affected patients. However, these previous neuroimaging studies have generally examined older patients, particularly those with major comorbidities known to affect functioning independent of diabetes. The primary aim of the current study was to examine the neural dynamics of selective attention processing in a young gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
3
9
0
Order By: Relevance
“…; Embury et al . ). Previous studies using modifications of the Eriksen flanker task have primarily characterized the role of medial prefrontal and anterior cingulate in conflict and error monitoring, while the role of more lateralized nodes is less well understood.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…; Embury et al . ). Previous studies using modifications of the Eriksen flanker task have primarily characterized the role of medial prefrontal and anterior cingulate in conflict and error monitoring, while the role of more lateralized nodes is less well understood.…”
Section: Discussionmentioning
confidence: 97%
“…Visual selective attention is often described as the capacity to discriminate and focus on visual features of interest within the larger visual field, while simultaneously inhibiting distracting visual input (Driver, 2001;Carrasco, 2011). Previous work has implicated a variety of regions important for this process, including but not limited to: lateral prefrontal cortex, medial prefrontal, anterior cingulate, superior parietal lobules, and the supplementary motor area (Botvinick et al 1999;Hazeltine et al 2000;van Veen et al 2001;Bunge et al 2002;Lau et al 2006;McDermott et al 2017;Lew et al 2018;Wilson et al 2018;Embury et al 2019). Previous studies using modifications of the Eriksen flanker task have primarily characterized the role of medial prefrontal and anterior cingulate in conflict and error monitoring, while the role of more lateralized nodes is less well understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, gray matter volume reductions and decreased white matter integrity have been found in T1D (Biessels and Reijmer, 2014; Moran et al, 2017), and the condition has been linked to widespread functional deficits in regional recruitment and network connectivity in the brain, particularly during episodic hypoglycemia (Bolo et al, 2011; Bolo et al, 2015; Musen et al, 2008; Rooijackers et al, 2016). Further, cortical dynamics have been shown to be altered in relatively healthy adults with T1D (i.e., without major comorbidities or complications) during attention- and working memory-related tasks, involving widespread cortical regions from parieto-occipital to frontal cortices (Embury et al, 2018a; Embury et al, 2018b). These studies have further shown that participants with T1D tend to recruit task-relevant brain regions more strongly, and utilize contralateral homologue areas to maintain adequate task performance, which may suggest compensatory processing in T1D.…”
Section: Introductionmentioning
confidence: 99%